Peran Bimbingan Konseling Pesantren dalam Meningkatkan Penguatan Karakter Siswa Madrasah Aliyah Baytul Mukarromah Watampone - Nurul Faizah Kamaruddin; Ardiansyah Ardiansyah (BADAN PENERBIT STIEPARI PRESS, 2024)
Islamic boarding school counseling guidance is a form of implementing services provided to help students or santri to develop into individuals who are independent, responsible, creative, productive and behave honestly through character strengthening education. The values that exist in character education are included in Islamic boarding schools' guidance and counseling services. The role of Islamic boarding school counseling is to instill the habit of practicing Islamic teachings in students or santri in daily life through the practice of worship. With program material covering faith, morals and worship. Forming character cannot be done in an instant by giving advice, orders, or instructions, but with the role of the Islamic boarding school guidance and counseling program. The formation of character requires an example, patience, habituation, and repetition. Thus, the process of education and character strengthening will be experienced by students or santri as a form of personality or self-character experience. The values of religious and moral life will strengthen the character of cooperation, time discipline, courage, and confidence in daily activities and learning processes. This is a step to gain knowledge and be able to apply knowledge in the form of skills work and as a positive attitude. From the results of this study, several important things were obtained regarding the role of Islamic boarding schools as a character strengthening program in madrasas. First, helping students or santri in dealing with the problems of everyday life. Second, giving motivation to students or students and teachers in order to build a spirit of enthusiasm for service. Third, implementing the results of coaching as a character education agenda. Meanwhile, based on the role played by a guidance and counseling teacher, namely the planning of Islamic boarding school guidance and counseling services, the implementation of Islamic boarding school guidance and counseling services, and the evaluation of Islamic boarding school guidance and counseling reports. services carried out with Islamic boarding school counseling to students or santri can form a spiritual and emotional soul with moral development as character strengthening.